Freight Integrator - ein Logistikkonzept mit Zukunft? - Seeck, Stephan; Smekal, Gerald (Deutscher Verkehrs-Verlag, 2004)
Bricht durch das neue Konzept des "Freight Integrators" eine neue Ära im intermodalen Transport an, oder handelt es sich dabei lediglich um "alten Wein in neuen Schläuchen"? Ist ein neuer Berufszweig im Entstehen, oder ist es eine Erweiterung bestehender oder gar nur ein neuer Begriff für bereits existierende Konzepte des multimodalen Transports? Wo liegen die Chancen, wo die Probleme für das Konzept? Der Artikel versucht, diese Fragen zu beantworten. difu

Based upon an idea described in the "White Paper on the European Transport policy until 2010" by the European Commission for Transport and Energy, addressing the integration of full loads on a door-to-door basis in an intermodal way, this article evolves a clear, yet open definition for the new term "Freight Integrator". Furthermore, it gives a comprehensive impression of the intermodal transportation market today, identifying possible professional fields that might be suitable to adapt this idea. Additionally, it is supposed to discover possibilities and difficulties for this new concept proposing ways to address them. The definition is developed with respect to the notions of the European Commission and professional fields in the intermodal transport market. At last recommendations to address existing problems that will help initiate the idea of the Freight Integrator are proposed. difu
Keywords: Verkehr; Güterverkehr; Verkehrsunternehmen; Zukunft; Logistik; Strategie; Rahmenbedingung; Problembereich; Transportgewerbe